A comprehensive experimental and modeling study of sulfur trioxide formation in oxy-fuel combustion. (August 2016) - Choudhury, Nujhat N.; Padak, Bihter
Highlights: Elevated concentration of SO3 in oxy-combustion systems leads to corrosion. SO3 temporal profiles were obtained by detailed kinetic modeling and experiments. SO3 formation is dominated by radicals. Complex interactions between SOx and NOx species exist. Abstract: This study focuses on the sulfur chemistry occurring within an oxy-combustion system by adopting a combined approach of detailed kinetic modeling and experiments. Influences of variable combustion parameters on SO3 generation have been investigated computationally by implementing different combustion mechanisms. Results indicated significant influences of the equivalence ratio, inlet SO2 concentration and presence of NO on SO3 formation while the inlet O2 concentration exhibited minimal effect. Presence of NO demonstrated different degrees of direct and indirect interactions between NOx and SOx species for different reaction sets. Sensitivity analysis indicated radicals to be playing a dominant role in SO3 formation. Collected temporal profiles of SO3 from the lab-scale combustion setup showed evidence of significant SO3 formation at temperatures as low as 650 K under realistic boiler temperature conditions. The equivalence ratio and the concentrations of SO2, O2 and NO were found to influence the SO3 formation. Predictions of final SO3 concentration from different mechanisms were comparable with the experimental data; however, the trend of the temporal profiles could not be anticipated by the models. Experiments conducted in the presence of NO indicated the existence of interactions between NOx and SOx species and also the requirement of modifications to the existing oxy-combustion models.